Atrial Fibrillation Termination Success During Ablation: Insights From Pooled Clinical Studies - Changjian He; Wenchang Zhang; Feng Li; Huaiqiang Wang; Xiongyi Han; Zihan Zhao; Guojie Ye; Tengfei Liu; Da Zhang; Haiyan Liu; Jie Liu; Jingning Zhao; et al. (Reviews in Cardiovascular Medicine)
Background: The optimal endpoint for ablation in persistent atrial fibrillation (pers-AF) remains unclear. This study aimed to systematically evaluate the prognostic value of acute AF termination in predicting the recurrence of arrhythmias. Methods: A systematic search of the PubMed, Cochrane Library, Web of Science, and Embase databases was conducted from inception to July 2023. Only studies with reports of acute termination for pers-AF and its predictive role in arrhythmia recurrence were included. Subgroup analysis was performed to identify potential confounders for the effect of AF termination. Results: A total of 22 studies were included in the meta-analysis. The pooled analysis indicated that acute termination of AF is significantly associated with an increased long-term success rate (relative risk (RR), 1.53; 95% CI, 1.41–1.66; p < 0.001; I2 = 35.4%). Moreover, subgroup analysis revealed that patients with an AF duration >12 months (RR, 1.92; 95% CI, 1.57–2.35; p < 0.001), aged >60 years (RR, 1.92; 95% CI, 1.60–2.31; p < 0.001) may derive benefits from AF termination during ablation. Interestingly, a significant interaction was observed in the study design subgroup, where multi-center studies showed a success rate of RR, 1.31 (95% CI, 1.14–1.50; p < 0.001), while single-center studies exhibited a higher success rate of RR, 1.65 (95% CI, 1.49–1.82; p < 0.001), with an interaction p-value of 0.008. Importantly, acute termination of AF did not significantly increase procedural complications (RR, 1.19; 95% CI, 0.59–2.39; p = 0.627; I2 = 0.0%). Conclusions: Our study suggests that AF acute termination during ablation for pers-AF provides a better long-term clinical outcome. The PROSPERO Registration: CRD42023431015, https://www.crd.york.ac.uk/PROSPERO/view/CRD42023431015.